PROSPEK PENGEMBANGAN WISATA DANAU BANDAR KAYANGAN LEMBAH SARI KOTA PEKANBARU - Wulandari, Sri; Putro, Tri Sukirno; Indrawati, Toti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study is to know the prospects of tourism development Kayangan Lake Bandar Lembah Sari Pekanbaru city, and to identify and analyze the factors driving and inhibiting the development of Bandar Kayangan Lake travel Lembah Sari Pekanbaru. The population in this study are all the visitors who come to Lake City Kayangan Lembah Sari Pekanbaru City in 2015. The sampling technique used is non-probability sampling is a sampling technique that does not give an opportunity or equal opportunity for each element or member of the population to be elected sample. Data is collected when visitors are in Lake City Kayangan Lembah Sari Pekanbaru. Determination of a minimum number of samples for the study was calculated based on a decent sample size between 30 - 500 in this study using a sample of 100 respondents. The results showed that the SWOT analysis in prospect in the development of Lake City Kayangan Lembah Sari is known that as a strength that is: Develop attractions clearly, Pendidikandan training in order to reduce costs in the operations of attraction, usage attractions computerized, cooperation with those who need Attraction , As a drawback, namely: Snag a job based on experience, A review of the potential attractions, There are no emergency procedures about tourist attractions, audit results on the attraction was not followed up. As Opportunity namely: The policy change agency to attractions, budget constraints for operational attractions, existence of the latest technology of attractions, attractions obtaining licensing requirement.Keyword : Prospects, Development, SWOT.